PENGATURAN TENTANG PARTISIPASI MASYARAKAT DALAM PEMBENTUKAN PRODUK HUKUM DAERAH - . Masriani (Jurnal LEX SPECIALIS, 2010)
Citizen is a decision variable, in the process law making or law enforcement in that case to gained a legality product that responsible to the citizen will, a law communication must be build in law planning, law making and law enforcement,regulation about participate of citizen right now is still generally so it must be explaiedn again in other regulation, for example is district regulation about mechanism of participate citizen in process of district regulationKey Note:Participate of citizen in law making process